Medication error in in-vitro fertilization assisted-twin pregnancy: A case report - Ravindra P. Choudhary, Neha Pethad, Srikanth Malavalli Siddalingegowda, Ashok Parameshwarappa (Journal of Applied Pharmaceutical Science, 2025)
The increase in infertility rates, particularly in India, comes with societal challenges, often targeting women. Assisted reproductive technologies like In-vitro fertilization (IVF) offer hope, but due to their intricate procedure and multiple medications, high risks of errors persist. Here, we report a case of a woman in her mid-30s undergoing IVF-assisted treatment, where an inadvertent medication error occurred, leading to subsequent complications. The patient was followed for 9 months following the incident of administration error. Multiple complications other than IVF-assisted inherent complication, can be reduced through collaborative efforts and interdisciplinary teams.
Keywords: Clinical outcomes, IVF treatment, medication error, pregnancy